(untitled) (KULT_online, 2011)
Since 2006 Prince Valiant has been released by Bocola, a German publishing house founded especially for the task. The complete edition presents Hal Foster’s tale, aesthetically very closely connected to the original Sunday comic strip appearing in the US since the late 1930s. Now the edition is accompanied by a Handbuch für Kenner und Liebhaber (orig.: The Definitive Prince Valiant Companion), which is not very scientific, but all the more impassioned. This enthusiastic accolade might be the first step for a serious scientific appreciation of Hal Foster’s work.